2008
DOI: 10.3750/aip2008.38.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of enzyme-producing bacteria in the digestive tracts of some freshwater fish

Abstract: Mondal S., Roy T., Sen S.K., Ray A.K. 2008. Distribution of enzyme-producing bacteria in the digestive tracts of some freshwater fish. Acta Ichthyol. Piscat. 38 (1): 1-8.Background. The information on gut microflora in fish is scanty and there is a paucity of knowledge regarding microbial enzyme activity in fish gastrointestinal tracts. Although some information is available on the enzymeproducing bacteria in fish digestive tracts, almost nothing is known about their distribution in different regions of the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 35 publications
(50 reference statements)
11
48
1
3
Order By: Relevance
“…Although, gut bacteria in catla were noticed to be dominated by the cellulolytic bacteria, existence of lipolytic, amylolytic, and proteolytic bacteria clearly advocated omnivorous feeding aptitude of the species as suggested elsewhere (Dasgupta 1996, Ghosh et al 2002a, Khabade 2015. Occurrence of higher numbers of heterotrophic enzyme-producing bacteria in DI region compared to the PI region was in agreement with the previous reports (Mondal et al 2008, Das et al 2014. This might indicate the possibility of microbial degradation of the food material in this part of the GI tract in assistance with the highly colonized enzyme-producing bacteria (Ghosh et al 2010).…”
Section: Discussionsupporting
confidence: 82%
“…Although, gut bacteria in catla were noticed to be dominated by the cellulolytic bacteria, existence of lipolytic, amylolytic, and proteolytic bacteria clearly advocated omnivorous feeding aptitude of the species as suggested elsewhere (Dasgupta 1996, Ghosh et al 2002a, Khabade 2015. Occurrence of higher numbers of heterotrophic enzyme-producing bacteria in DI region compared to the PI region was in agreement with the previous reports (Mondal et al 2008, Das et al 2014. This might indicate the possibility of microbial degradation of the food material in this part of the GI tract in assistance with the highly colonized enzyme-producing bacteria (Ghosh et al 2010).…”
Section: Discussionsupporting
confidence: 82%
“…In the present investigation, considerable populations of amylolytic and proteolytic bacteria were detected, which was in agreement with Mondal et al (2008) who reported amylolytic and proteolytic bacteria in the gastrointestinal tract of Nile tilapia correlating to its omnivorous feeding aptitude. Bairagi et al (2002) isolated an efficient protease-producing strain, TP3A from the gut of Oreochromis mossambica.…”
Section: Discussionsupporting
confidence: 80%
“…Several investigators have reported the presence of enzyme producing bacteria in the digestive tract of Oreochromis spp. (Sugita et al, 1997;Bairagi et al, 2002;Saha et al, 2006;Ray et al, 2007;Mondal et al, 2008;Sarkar and Ghosh, 2014;Sasmal and Ray, 2015). The present study is the first one demonstrating adherent bacteria and yeasts on the gut surfaces of Oreochromis niloticus along with antagonistic properties against the potential fish pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the gut microflora in fishes and crustaceans can metabolize several nutrients that the host cannot and can convert them to end products that are beneficial to the host (Suzer et al, 2007;Hoyoux et al, 2009). It has been reported that intestinal microorganisms have a beneficial effect on the digestive process of fish such as in the microbial breakdown of cellulose (Saha and Ray, 1998;Bairagi et al, 2002;Saha et al, 2006;Mondal et al, 2008;Ray et al, 2010), starch (Sugita et al, 1997), protein (Chong et al, 2002;Fu et al, 2005;Silvia et al, 2006) and lipid (Tanu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%